Merosesquiterpenes from marine sponge Smenospongia cerebriformis - Huyen, Le Thi; Thuy Hang, Dan Thi; Nhiem, Nguyen Xuan; Tai, Bui Huu; Tuan Anh, Hoang Le; Yen, Pham Hai; Dau, Nguyen Van; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2017)
Using various chromatography methods, three merosesquiterpenes belonging to sesquiterpene quinone type, neodactyloquinone (1), dactyloquinone D (2), and dactyloquinone C (3) together with two indole derivatives indole-3-aldehyde (4) and indole-3-cacboxylic methyl ester (5) were isolated from the methanol extract of the Vietnamese marine sponge Smenospongia cerebriformis. Their structures were determined by 1D-, 2D-NMR spectra, HR-ESI-MS and in comparison with those reported in the literature. Keywords. Smenospongia cerebriformis, merosesquiterpene, sesquiterpene quinone, indole derivative.